STRIP KOMIK SEBAGAI WADAH PERISTIWA BUDAYA - Savitri, Ayu Ida (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
Comic Strip is â€œa short series of amusing drawings with a small amount of writing which is usually published in a newspaperâ€ (Cambridge 2003: 239). It usually contains stories of what happened at the moment of the comic strips published in the newspaper. That is why, although it cannot be considered as a historical document, it can be considered as a medium of factual events happening at the moment of the newspaper published, delivered in an entertaining packaging. One of those factual events is cultural event related to the culture of the people where the newspaper published. Those events can be considered as cultural one by revealing the readersâ€™ interpretation of the comic strips by using semiotic and pragmatic theories to see whether the events is considered as part of their culture or not. As comic strip consists of pictures and utterances, the analysis can be done by using Semiotics theory to analyse its picture (visual element) and Pragmatics theory to analyse its utterance (verbal element). Firstly, the informant reveals the conversational implicature of the utterances. The result is then analysed by using the Relevance Theory from Sperber and Wilson (1986: 1996) to describe the utterancesâ€™ meaning, how they get it, and why they get it that way. Secondly, the informant interprets the comic strip (the picture along with the utteranceâ€™s analysis). The result is then analysed by using the Signifying Order Theory by Danesi and Perron (1999) to describe the comic stripâ€™s meaning, how they get it, and why they get it that way.